Linguistic Review on Marriage Age Regulation - Nuryani Nuryani; M Musyafa (Universitas Islam Negeri Jakarta, 2018)
Tis study fnds that the Indonesian Marriage Law, especially inthe section about the age of marriage, still contains the ambiguity in termsof the language. Tis leads to the gaps in the law that can potentially lead tothe violation of the law. It is stated in the Compilation of Islamic Law thatthe couple who have not reached the age of twenty should obtain a consentfrom both parents to marry. Based on this stipulation, every couple, whoare underage, can marry as long as they obtain their parent’s consent. Tispractice is not considered a violation of the law; the involving parties cannotbe penalized. Te article argues that there is a need to review the law to preventthe practice of underage marriage